2016
DOI: 10.2147/tcrm.s115253
|View full text |Cite
|
Sign up to set email alerts
|

Clinical prediction rules for failed nonoperative reduction of intussusception

Abstract: PurposeThe nonoperative reduction of intussusception in children can be performed safely if there are no contraindications. Many risk factors associated with failed reduction were defined. The aim of this study was to develop a scoring system for predicting the failure of nonoperative reduction using various determinants.Patients and methodsThe data were collected from Chiang Mai University Hospital and Siriraj Hospital from January 2006 to December 2012. Inclusion criteria consisted of patients with intussusc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…The study explored the possibility of prereduction outcome prediction by clinical and radiological parameters in cases of infantile intussusception. A study by Khorana and colleagues in 2016 in Thailand was the first attempt at a systematic construction of a clinical score for intussusception with the aim to be used as a predictive tool for non-surgical treatment of the condition 11. This current study validated the Khorana et al score using another set of data from a university hospital in the same country, but with different practice details.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The study explored the possibility of prereduction outcome prediction by clinical and radiological parameters in cases of infantile intussusception. A study by Khorana and colleagues in 2016 in Thailand was the first attempt at a systematic construction of a clinical score for intussusception with the aim to be used as a predictive tool for non-surgical treatment of the condition 11. This current study validated the Khorana et al score using another set of data from a university hospital in the same country, but with different practice details.…”
Section: Discussionmentioning
confidence: 80%
“…In Thailand, previous studies from our team and another study from Chiang Mai University (CMU) both found that low weight (<12 kg), prolonged symptoms, rectal bleeding, high body temperature, advanced invagination to the left side and unfavorable ultrasound findings were associated with failure of non-surgical reduction. Recently, researchers in CMU have constructed a scoring system for prediction of reduction failure called the ‘CMUI scoring system.’11 Their study demonstrated that a patient with intussusception with a high score (>11) had a significant likelihood of failed reduction. The objective of the current study was to validate the Chiang Mai University Intussusception (CMUI) scoring system with an independent external set of infantile intussusception data.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of intussusception is determined mostly with ultrasonography and per the clinical case definition for the diagnosis of acute intussusception proposed by the Brighton Collaboration Intussusception Working Group [ 4 ]. Although there are surgical and nonsurgical treatment modalities, less than 5% of the cases might be reduced spontaneously without any intervention [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Preoperative prediction of failed nonoperative management is important for selecting patients requiring preoperative evaluation and preparation for anesthesia and planning the therapeutic management. However, there are still no clear conclusions about factors that may predict the need for surgical treatment after failed therapeutic enema 7–9 . The aim of this study was to identify the preoperative factors that could reliably predict failure of nonoperative management in pediatric intussusception.…”
mentioning
confidence: 99%
“…However, there are still no clear conclusions about factors that may predict the need for surgical treatment after failed therapeutic enema. [7][8][9] The aim of this study was to identify the preoperative factors that could reliably predict failure of nonoperative management in pediatric intussusception.…”
mentioning
confidence: 99%